Processing of nanocellulose-based composites - Souza, S. F.; Ferreira, F. V.; Cherian, B. M. [UNESP]; Silva, V. R.; Manzato, L.; Pinheiro, I. F. (Elsevier, 2020)
Nanocomposite production using nanocellulose has been widely investigated based on all the features that nanocellulose can contribute to the composites properties, such as greater tensile strength, higher elastic modulus, higher viscosity, lower weight, barrier properties; it may work as catalyzer, modify the brittleness, change the glass transition in thermoset polymers among others. Meanwhile there are many challenges in this topic, mainly correlated to the incorporation of cellulose nanoparticles and how to get a good dispersion into the polymeric matrices. Therefore the nanocomposite preparation method is the key to obtain better properties and a good final material. Thus this chapter will deal with some strategies that are indispensable for the production of nanocellulose-based nanocomposites with good dispersion into thermoplastic and thermosetting polymers. Also some chemical modifications are discussed to improve the nanoparticles dispersion as well.
Keywords: casting method; cellulose nanocrystals; Chemical modification; extrusion; melting process; nanofibers; nanofibrillated; nanofibrils; rheological properties